Argot in the Motorcycle Buying and Selling Forum on Facebook as a Buying and Selling Strategy : A Sociolinguistic Study - Annafi, Ghilman Ghani; Muharudin, Eko (CV. Tripe Konsultan, 2024)
Language has an important role in daily life, especially for communication between humans, including in buying and selling activities on social media, therefore the researcher conducted a study to reveal how the form and meaning of argot develops in the motorcycle buying and selling forum on Facebook, as well as how its use plays a role in strengthening social dynamics and community identity and this study aims to describe the use of argot in the motorcycle buying and selling forum that available on the Facebook platform. Argot, as a special form of language used by certain groups, in addition to this study is also to help members of the motorcycle buying and selling community to improve their strategies in terms of buying and selling and help increase knowledge for ordinary people, Through the study of sociolinguistic studies, this study examines the forms and meanings used by forum members, as well as their implications for social dynamics and interactions between members. This study uses a qualitative method with a descriptive approach and content analysis from posts in the facebook forum for buying and selling CB/GL/TIGER motorcycles in the Purbalingga, Banjarnegara and Purwokerto areas. Data was collected through the ability to see and record techniques on posts and buying and selling interactions in the forum. The results of the study show that the use of argot in this forum not only serves as an effective communication tool, but also as a symbol of identity and solidarity of the motorcycle loving community. Researchers found 16 forms of argot and divided into 3 types, namely the discovery of 5 phrases, 12 abbreviations, 3 sentences. These findings confirm the importance of understanding the role of language in the formation and maintenance of online communities, as well as provide further insights into sociolinguistic dynamics in the digital realm.